Exploring English Vocabulary Enhancement In Indonesian EFL Students: Case Study Analysis of Mastery of Subtitle Film In Senior High School - Napa , Siti; Kristiawan, Dana Yudha; Setyawan, Mochamad Ardi (English Language Teaching Methodology, 2025)
This study explores the impact of subtitles in movies on English vocabulary acquisition among EFL learners at a secondary school in Indonesia. Using a qualitative approach and a case study design, this study examined the vocabulary learning experiences of sixth-grade X1 students in one high school in East Java. The data collected over one semester included vocabulary test observations, semi-structured interviews using ten directed essay questions, and reflection notes to capture students' perceptions and learning strategies. Thematic data analysis showed that the use of movie subtitles is in both English and Bahasa Indonesia. Significantly facilitated vocabulary acquisition through simultaneous exposure to audio and text, contextualized word meanings, and natural repetition of language input. The findings of this study highlight several important aspects: (1) English subtitles help students recognize word forms and spelling, while Indonesian subtitles support the understanding of the overall meaning. (2) Students develop self-learning strategies such as pausing, repeating parts of the film, switching subtitle modes, and taking notes on new vocabulary. (3) Learning motivation and engagement are enhanced when the films viewed match students' interests and are accompanied by interaction with peers. However, they have encountered challenges, including dialogue that is too fast, a mismatch of subtitles with audio, and difficulty understanding idioms or indirect expressions. The study concludes that movie subtitles are an effective and engaging medium for vocabulary development, provided they are supported by proper scaffolding, learner awareness, and access to quality audiovisual materials.